A strategy to enhance VOC of π-conjugated molecules based on thieno[2, 3-b] indole for applications in bulk heterojunction organic solar cells using DFT, TD-DFT, and 3D-QSPR modeling studies. (9th December 2022) - El Mouhi, Rahma; Daoui, Ossama; Fitri, Asmae; Benjelloun, Adil Touimi; El Khattabi, Souad; Benzakour, Mohammed; Mcharfi, Mohammed; Kurban, Mustafa
Abstract : The electronic structure and optical properties of eight novel molecules based on 8-alkyl-8 H -thieno[2, 3- b ] indole was determined using density functional theory DFT, TD-DFT and 3D-QSPR. Abstract : Seven novel organic compounds BHJ- i ( i = 1–7) based on carrying 8-alkyl-8 H -thieno [2, 3- b ] indole as a donor, thiophene as a bridge and different acceptors were used for bulk heterojunction organic solar cells (BHJ). The main objective of this work was to find a better acceptor for π-conjugated molecules used in photovoltaic solar cells in order to improve their efficiency. The study was through DFT and TD-DFT quantum methods. Several optoelectronic properties of these materials, electronic properties ( E HOMO, E LUMO, and E gap ), natural bond orbital (NBO) analysis, quantum chemical parameters (chemical hardness ( η ), chemical potential ( μ ) and electronegativity ( χ )), UV-vis spectra and the open-circuit photovoltage ( V oc ), were calculated. We also developed the 3D-QSPR model based on CoMFA and CoMSIA approaches to predict the most important three-dimensional properties of the structure of 8-butyl-8 H -thieno [2, 3- b ] indol-2-yl) thiophen-2-yl) methylene derivatives, which allowed us to design new molecules and optimize their properties for a high-performance V oc . The results indicated that the molecules in this work exhibit a theoretical power conversion efficiency of 7%. Finally, due to 3D-QSPR results, we have designed 10 new molecules, which have very interesting V oc values.